2021
DOI: 10.1007/s13770-021-00348-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Cell Cultures as a Research Platform in Lung Diseases and COVID-19

Abstract: Background: Chronic respiratory diseases (CRD) are a major public health problem worldwide. In the current epidemiological context, CRD have received much interest when considering their correlation with greater susceptibility to SARS-Cov-2 and severe disease (COVID-19). Increasingly more studies have investigated pathophysiological interactions between CRD and COVID-19. Area covered: Animal experimentation has decisively contributed to advancing our knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 119 publications
0
10
0
Order By: Relevance
“…Three-dimensional (3D) cell-culture models based on primary cells are acquiring great importance as a new and robust platform for studying complex biological processes and might be a promising alternative in C. trachomatis pathogenetic studies [ 13 ]. In this regard, 3D models might help in recreating the microenvironment that C. trachomatis encounters in the host tissue, allowing a deeper understanding of host–pathogen interactions since these systems promote direct cell-to-cell contact, interactions of cells with the extracellular matrix and in vivo like exchange of soluble factors [ 10 , 11 ]. Furthermore, 3D cell culture models are known to retain the cellular structure and spatial orientation more closely resembling the in vivo parental tissue than the more widespread 2D cell culture models [ 10 , 11 ].…”
Section: Current Advances In Three-dimensional Cell-culture Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Three-dimensional (3D) cell-culture models based on primary cells are acquiring great importance as a new and robust platform for studying complex biological processes and might be a promising alternative in C. trachomatis pathogenetic studies [ 13 ]. In this regard, 3D models might help in recreating the microenvironment that C. trachomatis encounters in the host tissue, allowing a deeper understanding of host–pathogen interactions since these systems promote direct cell-to-cell contact, interactions of cells with the extracellular matrix and in vivo like exchange of soluble factors [ 10 , 11 ]. Furthermore, 3D cell culture models are known to retain the cellular structure and spatial orientation more closely resembling the in vivo parental tissue than the more widespread 2D cell culture models [ 10 , 11 ].…”
Section: Current Advances In Three-dimensional Cell-culture Modelingmentioning
confidence: 99%
“…In the literature, several approaches have been developed for generating 3D models (Table 1), including scaffold-based 3D cultures, that use matrices for cells adhesion, and non-scaffold 3D cultures, that, by contrast, lead to cell assembly into spheroids. The nonscaffold 3D cultures promote cell-to-cell rather than cell-to-extra cellular matrix interactions, favoring the natural aggregation and assembly of cells in spheroids that better mimic the in vivo organ formations, hence the name organoids [10,11,46]. Amongst the different methodologies, 3D bioprinting technologies have opened a completely new field for tissue engineering [47].…”
Section: Current Advances In Three-dimensional Cell-culture Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent to completion of these studies, a comprehensive meta-analysis could derive an effective MSC-EVs based therapeutic regime for the management of acute lung injury in the context of COVID19. Several notable works have been reported recently on various aspects of stem cells and exosomes in the context of COVID19 [ 20 23 ]. However, this review standout as a unique collection of the current landscape in terms of preclinical, clinical and patent data sets reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Though it has been described that the SARS-CoV-2 establishes an interaction with host cells through the angiotensin-converting enzyme 2 (ACE2) receptors (Zhang et al, 2021), other reports suggest that the virus can infect any epithelial cells of the oropharyngeal mucosa and respiratory tract, including endothelial cells, especially in severe disease and ARDS condition after cytokine storm irrespective of the presence of ACE2 receptors (Zamorano Cuervo & Grandvaux, 2020; Liu et al, 2021). Organoid culture (2D and 3D) studies on human bronchial and lung epithelial cells revealed no SARS-CoV-2 cellular tropism or ultrastructural alteration (Elbadawi & Efferth, 2020; Salahudeen et al, 2020; da Silva da Costa et al, 2021). Transmission (for cellular ultrastructure) and scanning (for surface ultrastructure) electron microscopic and immunofluorescence (for analysis of cellular infection) studies can directly explore the SARS-CoV-2 infection in different cells of bronchoalveolar fluid (BALF), that provide direct evidence of cellular infection load and ultrastructural changes in old and young patients with comorbidities such as diabetes, liver and kidney diseases, and malignancies.…”
Section: Introductionmentioning
confidence: 99%